The new “dual osteotomy”: combined open wedge and tibial tuberosity anteriorisation osteotomies - Megied, Wael Samir Abdel (Springer-Verlag, 2009)
The high frequency with which medial compartment osteoarthritis is associated with patellofemoral osteoarthritis makes the addition of tibial tuberosity anteriorisation to high tibial osteotomy an appealing solution, despite the discouraging previously reported long-term results when tubercle anteriorisation was combined with a Coventry closed wedge technique. We conducted a prospective study of a new osteotomy combination: “the dual osteotomy”. An open wedge high tibial osteotomy was combined with 1- to 1.5-cm Maquet-like tibial tuberosity anteriorisation. Thirty-four knees in 30 patients underwent surgery, including ten knees in nine male patients and 24 knees in 21 female patients with a mean age of 45 years (age range 34−58 years). All patients had varus medial compartment osteoarthritis and patellofemoral osteoarthritis with preoperative anatomical tibiofemoral angle exceeding 5°. Twenty-four months after surgery, final evaluation detected improvement in the Knee Society clinical rating system function score from a mean of 61.3 (range 30−80) preoperatively to a mean of 87.3 (range 50−100) postoperatively and in the knee pain score from 27.3 (range 10−30) to 47 (range 30−50) postoperatively. Based on the rating system, at final follow-up, 70% of patients experienced no pain, 13% had mild or occasional pain, 10% had pain on stairs only, and 7% had pain during walking and on stairs. Anatomical tibiofemoral angles from 0 to 10° valgus were achieved in 91% of operated knees, and union was achieved in all cases within six to twelve weeks after surgery. The dual osteotomy was effective in the short term in cases of medial compartment osteoarthritis associated with patellofemoral osteoarthritis.